Update on Essential Hypertension 2016
DOI: 10.5772/64104
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity in Essential Hypertension

Abstract: The prevalence of essential hypertension has continued to increase worldwide, and its consequences have remained a growing concern. A number of sociodemographic and clinical variables may however serve as key determinants of the extent to which it is associated with psychiatric comorbidity as well as impairment of quality of life. The aim of this study, therefore, was to determine the sociodemographic and clinical factors that may influence the level of psychiatric comorbidity and quality of life associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 85 publications
(141 reference statements)
1
8
0
Order By: Relevance
“…Among people living with chronic medical diseases, the study showed findings similar with those of other studies carried out in Ethiopia (63.3%) [ 24 ], Pakistan (60.2%, [ 25 ], Nigeria (64.4%) [ 26 ], and Delhi India (58.7%) [ 27 ]. However, the magnitude of psychological distress in this study was higher than that in studies done in Southern Ethiopia (39.2%) [ 28 ], Addis Ababa, Ethiopia (53.1%) [ 29 ], India (50.8%) [ 30 ], Kenya (42.3%) [ 31 ] and Iran (14%) [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…Among people living with chronic medical diseases, the study showed findings similar with those of other studies carried out in Ethiopia (63.3%) [ 24 ], Pakistan (60.2%, [ 25 ], Nigeria (64.4%) [ 26 ], and Delhi India (58.7%) [ 27 ]. However, the magnitude of psychological distress in this study was higher than that in studies done in Southern Ethiopia (39.2%) [ 28 ], Addis Ababa, Ethiopia (53.1%) [ 29 ], India (50.8%) [ 30 ], Kenya (42.3%) [ 31 ] and Iran (14%) [ 32 ].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, it was found that selfreported diagnosis of hypertension is commonly correlated with 12-month anxiety disorders and other comorbid mental disorders among South Africans as compared to those without hypertension. Delving further into socioeconomic and demographic risk factors, hypertension prevalence has been associated with low income, and specifically, the higher the income was in the cited study, the lower the prevalence of psychiatric comorbidity was in hypertension patients [1]. Thus, the risk of developing a mental disorder comorbid to hypertension appears to increase in lowincome populations.…”
Section: Hypertension and Anxietymentioning
confidence: 89%
“…In addition to health consequences and health-related risk factors, the growing prevalence of hypertension has led to a wide array of psychiatric comorbidities and thus, impairment of quality of life [1]. One of the most commonly diagnosed comorbidities of hypertension are anxiety disorders, which is the primary focus of this paper.…”
Section: Hypertension and Anxietymentioning
confidence: 99%
See 2 more Smart Citations